Student’s critical thinking ability in completing metacognition problems of mathematical education students in Balikpapan University - rahayu Sri Waskitoningtyas; Ganjar Susilo (STKIP PGRI Banjarmasin, 2020)
This study aims to identify students' critical thinking skills in solving metacognition problems at the University of Balikpapan Mathematics Education Study Program. The research approach that will be used by researchers is a quantitative descriptive approach. Taking research subjects on mathematics education students who were given questions about metacognition Trigonometry material. Data collection techniques using triangulation are documentation in the form of student answers, observations of student answers sheets, and interviews. Of the 8 questions tested 6 questions that were worthy of use (questions number 1, 2, 4, 5, 6, and 7) with r11 = 0,82 (items were said to be good). Then the 6 questions were given to Mathematics Education students totaling 25 students. Research results show that in question number 1 as many as 19,53% of students are able to do this value of 108. For question number 2 as much as 19,17% of the value 106. While the question number 4 is 19,26% of the value 106. As many as 18,26% of students for question number 5 with a value of 112. In question number 6 as many as 13,92% of students with a value of 98. For question number 7 obtained 9.76% of students from a value of 71.